Redefining the risks of prenatally ascertained supernumerary marker chromosomes: a collaborative study. Issue 8 (1st August 2006) - Graf, M D; Christ, L; Mascarello, J T; Mowrey, P; Pettenati, M; Stetten, G; Storto, P; Surti, U; Van Dyke, D L; Vance, G H; Wolff, D; Schwartz, S
Abstract : Background: A marker chromosome is defined as a structurally abnormal chromosome that cannot be identified by routine cytogenetics. The risk for phenotypic abnormalities associated with a marker chromosome depends on several factors, including inheritance, mode of ascertainment, chromosomal origin, and the morphology, content, and structure of the marker. Methods: to understand the karyotype-phenotype relationship of prenatally ascertained supernumerary de novo marker chromosomes, we combined data from prenatal cases obtained from 12 laboratories with those from studies in the literature. We were able to obtain cytogenetic and phenotypic data from 108 prenatally ascertained supernumerary de novo marker chromosomes to refine the phenotypic risk associated with these markers. Because of the growing number of cases and because more techniques are available to delineate marker morphology, we have been able to group risk estimates into subcategories, such as by marker type and whether there are ultrasound abnormalities. Results: If a de novo supernumerary marker chromosome is found prenatally, our data suggest there is a 26% risk for phenotypic abnormality when there is no other information defining the marker (such as chromosomal origin or information about the existing phenotype). However, if high resolution ultrasound studies are normal, this risk reduces to 18%. Conclusions: Our findings strongly support the value of additional genetic studies for more precisely defining the risk in individual cases involving marker chromosomes.